Association between TSPO-PET measurable microglial activation and soluble GFAP in multiple sclerosis - Tirkkonen, Inke (My University, 2023)
INTRODUCTION Multiple sclerosis (MS) is a chronic, immune-mediated disease that targets the central nervous system (CNS). It is characterized by neuroinflammation, demyelination, and progressive neurodegeneration which are believed to be triggered by an autoimmune reaction. Despite recent advancements, the pathophysiology of MS is still not fully understood. Microglia and astrocytes are glial cells of the CNS. Microglia participate in the surveillance of the CNS and react accordingly in case of a disturbance, causing them to change their phenotype in a phenomenon called microgliosis. Activated microglia produce various pro- and anti-inflammatory agents, attracting more immune cells to the site. Like microglia, astrocytes can become activated in a process called reactive astrogliosis, characterized by a changed gene expression and hypertrophy. Reactive astrogliosis can result in the formation of a glial scar. Together microglia and astrocytes drive the MS pathophysiology by partaking in lesion formation, causing tissue damage due to the neurotoxic agents they release, and on the other hand by controlling the neuroinflammation. STUDY OBJECTIVE AND DESIGN The objective of this study was to evaluate microglial and astrocytic activation in MS patients and shed light on the possible connections between the two. Microglial activation was assessed by TSPO-PET imaging using a [11C]PK11195 radioligand, and serum glial fibrillary acidic protein (GFAP) was used as a biomarker of astrocytic activity. The study cohort included 44 MS patients who took part in PET and magnetic resonance imaging, blood sampling, and clinical assessment. In addition, 22 healthy controls (HCs) were included. RESULTS MS patients had a mean serum GFAP of 98.85 pg/ml and HCs 69.15 pg/ml (p = 0.006). The serum GFAP was lower in treated patients compared to non-treated (p = 0.005). In MS patients compared to HCs, [11C]PK11195 binding, presented as distribution volume ration (DVR) and the number of active voxels, was higher in whole brain (p = 0.011, p = 0.020) and normal appearing white matter (NAWM) (p = 0.046, p = 0.010). MS patients were divided into GFAP(low) and GFAP(high) groups based on the 80th percentile serum GFAP of HCs (90.47 pg/ml). Patients with high serum GFAP levels had fewer active voxels in whole brain (p = 0.026) and NAWM (p = 0.023), as well as lower DVR in cortical grey matter (p = 0.003), compared to patients with low serum GFAP. The DVRs in brain stem (p = 0.049), pallidum (p = 0.042), and ventral diencephalon (p = 0.048) were in turn higher in patients with high serum GFAP. In MS patients, serum GFAP correlated with Extended Disability Status Scale (EDSS) (ρ = 0.38, p = 0.012). High GFAP levels were associated with high volume-percentage of overall-active lesions (ρ = 0.30, p = 0.046) in all MS patients. Serum GFAP correlated negatively with the volume-percentage of inactive lesions in GFAP(high) group (ρ = -0.50, p = 0.012), and there was a trend towards significance in the whole MS population (ρ = -0.29, p = 0.056). CONCLUSION In conclusion, microglial and astrocytic activity are increased in MS as indicated by increased [11C]PK11195 binding and serum GFAP. Serum GFAP correlated with EDSS, suggesting it being indicative of disease progression. However, unambiguous conclusions on the association between serum GFAP and [11C]PK11195 binding cannot be drawn as correlations were quite weak, and both positive and negative in nature suggesting the association could be dependent on the brain region. To confirm these results and fully understand the association between microglial and astrocytic activation, more research is required. Key words: Multiple Sclerosis, Microglial activation, GFAP, TSPO-PET.
Keywords: Multiple Sclerosis, Microglial activation, GFAP, TSPO-PET